Pengaruh Harga, Keamanan, Dan Ketepatan Waktu Pengiriman Pada Keputusan Penggunaan Layanan J&T Express Di Kota Jambi - Hassandi, Irfan; Desy Ratna Wijaya; Ivan Cristhian; Pangestu, Mira Gustiana; Fadillah, Yosi; Yossinomita, Yossinomita (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This study used a random probability sampling technique to determine how customer decisions about J&T Express delivery services in Jambi City are influenced by pricing, security, and the promptness of product delivery. Data for this study, which employs quantitative methods, was gathered using a questionnaire. One hundred respondents from Jambi City who had utilized delivery services and analyzed their data using the SPSS software made up the research sample. The study's findings demonstrated that (1) Price had a positive and significant influence, with a significant value of 0.023. (2) Security had a favorable but not statistically significant impact on the decision to employ J&T Express delivery services in Jambi City, as indicated by its significance value of 0.617. (3) A significant value of 0.000 was achieved for the timeliness variable. Timeliness plays a major role in the decision to employ J&T Express services in Jambi City, and it has a positive impact. Price and timeliness are the most important factors when choosing to use J&T Express delivery services in Jambi City, according to data collected for this study.